Pak-US Security Relation: Challenges & Prospects for Pakistan - Faiza Bas, Ghulam Mustafa (JSSH, 2023)
Survival and independence are the essential ingredients of the existence of a community, society, nation and state. Both are being processed through security mechanism and policies by the nation’s status in international politics. Therefore, security is multifaceted phenomenon based on requirements, competence and qualms of intermingling entities. Security can also be understood as freedom from all kinds of fears. Security is a concept that is not only dependent on external factors but it is also dependent on psychological orientations of the people.